Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijerph16111909
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Abilities of Professional Handball Players

Abstract: The main purpose of the paper was to evaluate selected psychomotor abilities of handball players depending on the competition class (league), position on the court, training seniority and the dominant hand. The study covered a group of 40 handball players (age: 24.02 ± 3.99), while 50 non-training men (age: 22.90 ± 1.13) formed the control group. Studies were performed using Test2Drive computer tests. The following four tests were used for measuring psychomotor fitness: simple reaction time test, choice reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 34 publications
5
22
1
Order By: Relevance
“…The present study further demonstrated that a difference existed in hand-eye coordination between the Premier League and First Division rugby players. The findings of Paul et al (2011), and Przednowek et al (2019) concur with the current study and also found differences in handeye coordination between expert and novice table tennis players, and handball players, respectively (23,24). Experts athletes generally have better skill, accuracy and spatio-temporal constraints on visual information acquisition, which leads to enhanced hand-eye coordination, and thus improved athletic performance (24).…”
Section: Speed Of Recognition Of Premier League Rugbysupporting
confidence: 88%
“…The present study further demonstrated that a difference existed in hand-eye coordination between the Premier League and First Division rugby players. The findings of Paul et al (2011), and Przednowek et al (2019) concur with the current study and also found differences in handeye coordination between expert and novice table tennis players, and handball players, respectively (23,24). Experts athletes generally have better skill, accuracy and spatio-temporal constraints on visual information acquisition, which leads to enhanced hand-eye coordination, and thus improved athletic performance (24).…”
Section: Speed Of Recognition Of Premier League Rugbysupporting
confidence: 88%
“…In the future the studies can be extended to the comparison of youth training football with a non-training group. The other scientists have shown that people training various sports are characterized by a faster simple reaction, which shows that through sports training we are able to improve this ability [ 11 , 15 , 18 , 21 , 28 , 55 , 56 , 57 , 58 , 59 ]. Ando et al [ 32 ] confirmed that thesis during their research, showing that players who train football have faster reaction time than those who do not train.…”
Section: Discussionmentioning
confidence: 99%
“…Sports disciplines at the highest level require the best psychomotor preparation of players because every detail can affect the final sports result [ 15 , 16 ]. There are many studies confirming that players practicing various sports disciplines are characterized by a better level of cognitive abilities than non-training people [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even when serving a player, a player must also be able to coordinate his eyes and hands so that the contact between the bed and the ball has the right timing, so that the ball's rotation, ball speed, and placement can be carried out correctly (Paul, Biswas, & Sandhu, 2011). A study explains that the speed of eye-hand coordination cannot be done perfectly if the athlete experiences an injury to the neck, without eye movement assisted by agile neck rotation, good eye-hand coordination cannot be obtained so that the athlete will also have difficulty serving (Mutasim, Stuerzlinger, & Batmaz, 2020;Przednowek, et al, 2019) The relationship between concentration and eye-hand coordination with the accuracy of backhand backspin service Based on data analysis conducted with Pearson product moment correlation, the level of relationship between concentration and eye-hand coordination with backhand backspin service accuracy is 0.55, which means that the level of relationship between the two variables is in the sufficient category.…”
Section: Nomentioning
confidence: 99%
“…When the crucial points are that the athlete should not make mistakes and the athlete makes mistakes, it will clearly have an impact on defeat. Therefore how the role of concentration when athletes perform services must be known, as well as the contribution of eye-hand coordination, which plays a very important role in providing service, must also be known by both the athlete and the coach himself, this is useful for considering the development of a training program so that accuracy service becomes more accurate and consistent (Mutasim, et al, 2020;Przednowek, et al, 2019). Feelings of bad performance in competition are more often found in female athletes and athletes who are old (Grossbard, Smith, Smoll, & Cumming, 2009).…”
Section: Nomentioning
confidence: 99%